Unlocking the tumor-immune microenvironment in osteosarcoma: insights into the immune landscape and mechanisms - Orrapin, Santhasiri; Moonmuang, Sutpirat; Udomruk, Sasimol; Yongpitakwattana, Petlada; Pruksakorn, Dumnoensun; Chaiyawat, Parunya (Frontiers in Immunology, 2024)
Osteosarcoma has a unique tumor microenvironment (TME) located within the bone marrow (BM), which is characterized by its highly dynamics and comprises bone cells, immune cells, stromal cells, and heterogeneous vascular structures. These elements are intricately embedded in a mineralized extracellular matrix, setting it apart from other primary tumor microenvironments. In a state of normal physiological function, these cell types collaborate in a coordinated manner to maintain the homeostasis of both the bone and hematopoietic systems. However, in the pathological condition i.e. neoplastic malignancies, the tumor-immune microenvironment (TIME) has been shown to promote to not only uncontrollably proliferate, migrate, resist apoptosis and drugs, but also help tumor cells escape immune surveillance. The intricate and dynamic system of the tumor immune microenvironment in osteosarcoma involves crucial roles played by various infiltrating cells, the complement system, and exosomes. This complexity is closely associated with tumor cells evading immune surveillance, experiencing uncontrolled proliferation, and facilitating metastasis. In this review, we elucidate the intricate interplay between diverse cell populations in osteosarcoma-TIME, each contributing uniquely to tumor progression. From chondroblastic and osteoblastic osteosarcoma cells to osteoclasts, stromal cells, and various myeloid and lymphoid cell subsets, the comprehensive single-cell analysis provides a detailed roadmap of the complex osteosarcoma ecosystem. Furthermore, we summarize the mutations, epigenetic mechanisms and extracellular vesicles that dictate the immunologic landscape and modulate the TIME of osteosarcoma. The perspectives of clinical implementation of immunotherapy and therapeutic approaches for targeting immune cells are also intensively discussed.